Trade Policy Reforms for the Twenty First Century : The Case of Nepal - Narain, Ashish; Varela, Gonzalo (World Bank, Washington, DC, 2017)
This report examines how Nepal could move away from a remittance-driven growth model by reforming its trade policies to increase competitiveness. It looks at the extent to which Nepal has been tapping into its trade potentials, the underlying obstacles that it faces, and the type of reforms that could turn trade and investment into a vehicle for growth. Five key messages emerge. First, Nepalese exporters remain small and struggle with increase their shipments once they enter a new market, rather than with the fixed cost associated with entering. This is due to severe supply-side constraints that affect their trade and production costs. Second, Nepalese firms underutilize existing trade agreements and granted trade preferences. Third, diversification opportunities lie in fast-growing economies in East Asia and the Pacific. Efforts regarding connectivity, trade facilitation and export intelligence could help firms get to those markets. Fourth, to reduce the anti-export bias of its trade policy, Nepal needs to simplify its tariff code, reduce tariffs on intermediates, and embrace deeper integration, starting with more openness to services and investment. Fifth, trade reforms in Nepal are welfare enhancing and, on average, pro-poor.